Sustainable Strategies for Business and Economic Development in the 21st Century - Hurley, Brian (New York Willford Press, 2016)
Human activities like business have a tremendous impact on the ecology. The role of sustainable business set-ups is to keep a check on these ecological impacts. This book is intended to serve as a valuable reference on all topics concerned with business and economic sustainability. It is a collective contribution of internationally renowned experts of this discipline encompassing a wide gamut of topics in a coherent manner. Some of the topics that have been covered include techniques to minimize environmental impact, strategies for corporate sustainability, corporate social responsibility, etc. This book is highly recommended for students, academicians and professionals pursuing economics and allied fields of study.
Keywords: Business; Economics